An Exploratory Study: Mobile Device Use For Academics - Malia Hoffmann (Research in Social Sciences and Technology- OpenED Network, 2017)
This exploratory study surveyed how undergraduate students and higher education instructors at two small faith-based universities in Southern California used mobile devices in and outside of the class for academic purposes. The researcher cross-referenced the results from the two groups to make correlations. The results of this study showed that nearly all instructor participants had multiple devices and almost half of the student participants had two or more devices as well. Those devices are being used in and outside of formal class for academics in very basic and emerging way that are just touching the surface of their capabilities. This study found that students use their devices in class to read, reference, or search materials. Faculty reported using their devices as presentation devices most often.